A comparison of song‐lyric and prose self‐instruction procedures for increasing novel skills in children. Issue 1 (12th March 2019) - Bloom, Lorraine B.; Kettering, Tracy L.; Walker, Diana
Abstract : We compared the effects of the effects of self‐instructions in the form of prose or song lyrics in the acquisition of gross motor tasks in 4 third‐grade children. We taught participants 4 pairs of gross motor tasks, with one task in each pair taught with prose self‐instructions and the other taught with song lyric self‐instructions. Both self‐instruction procedures were effective for teaching tasks; however, acquisition was quicker with song lyric self‐instruction for 4 task pairs, acquisition was quicker with prose self‐instruction for 3 task pairs; and similar for 1 task pair. Participants were then able to select their preferred method of self‐instruction for a novel, applied skill. Two participants selected song‐lyric self‐instructions and 2 participants selected prose self‐instructions.